2023
DOI: 10.1002/ajhb.23862
|View full text |Cite
|
Sign up to set email alerts
|

Sex segregation in strength sports: Do equal‐sized muscles express the same levels of strength between sexes?

Abstract: Objectives: Concerns have been raised against the current two-sex binary category in sports competitions. The thesis states that if males and females were separated based on muscle size, it would negate the strength advantage between the sexes. We tested the possible sex differences in various strength outcomes when pair-matched for muscle thickness. Methods: A total of 16 different data sets (n = 963) were assessed to pairmatch females with males who had a muscle thickness value within 2%. We further compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
3
0
1
Order By: Relevance
“…Considering females muscle testing, it worth noting that the strength characteristics of males and females' muscle are different. Males and females with the same muscle size show different levels of strength, being females' quadriceps muscles weaker by a 12% to 24 % in comparison to male's when normalized for muscle thickness [23]. Furthermore, knee injuries rate risk is higher in females than in males due to the morphological condition of "genus valgus" [42], in fact, the prevalence of knee injuries in females is further worsened by the presence of the valgus knee, which is a common feature in the female Asian biotype [18].…”
Section: Introductionmentioning
confidence: 99%
“…Considering females muscle testing, it worth noting that the strength characteristics of males and females' muscle are different. Males and females with the same muscle size show different levels of strength, being females' quadriceps muscles weaker by a 12% to 24 % in comparison to male's when normalized for muscle thickness [23]. Furthermore, knee injuries rate risk is higher in females than in males due to the morphological condition of "genus valgus" [42], in fact, the prevalence of knee injuries in females is further worsened by the presence of the valgus knee, which is a common feature in the female Asian biotype [18].…”
Section: Introductionmentioning
confidence: 99%
“…Considering females muscle testing, it worth noting that the strength characteristics of males and females muscle are different. Males and females with the same muscle size show different levels of strength, being females' quadriceps muscles weaker by a 12% to 24 % in comparison to male's when normalized for muscle thickness [10]. Furthermore, knee injuries rate is higher in females than in males due to the morphological condition of "genus valgus" [11], in fact, the prevalence of knee injuries in females is further worsened by the presence of the valgus knee, which is a common feature in the female Asian biotype [12].…”
Section: Introductionmentioning
confidence: 99%
“…;Castro et al, 1995;Heyward et al, 1986;Nimphius et al, 2019;Roberts et al, 2020;Schantz et al, 1983;Welle et al, 2008). Interestingly, in powerlifters,Kataoka et al (2023) found that men were stronger than women even after matching groups for muscle thickness, suggesting that in lifting sports (e.g., Olympic Weightlifting and Powerlifting), men may have greater strength relative to muscle mass. Although muscle mass was not quantified in the present study, greater body weight in resistance trained individuals does tend to result in greater underlying muscle mass, which may be evident in IWF competitors.…”
mentioning
confidence: 99%